2007
DOI: 10.1111/j.1365-2958.2007.05704.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pyogenes pili promote pharyngeal cell adhesion and biofilm formation

Abstract: SummaryGroup A Streptococcus (GAS, Streptococcus pyogenes) is a Gram-positive human pathogen responsible for several acute diseases and autoimmune sequelae that account for half a million deaths worldwide every year. GAS infections require the capacity of the pathogen to adhere to host tissues and assemble in cell aggregates. Furthermore, a role for biofilms in GAS pathogenesis has recently been proposed. Here we investigated the role of GAS pili in biofilm formation. We demonstrated that GAS pilusnegative mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
208
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(221 citation statements)
references
References 48 publications
13
208
0
Order By: Relevance
“…Although important data have been published on their biogenesis and their function (Abbot et al, 2007;Dramsi et al, 2006;Gianfaldoni et al, 2007;Lauer et al, 2005;Maisey et al, 2007;Manetti et al, 2007;Mora et al, 2005;Rosini et al, 2006;Scott & Zähner, 2006;Telford et al, 2006), little is known about the regulation of their synthesis. Besides RogB (Dramsi et al, 2006;Gutekunst et al, 2003) SrtA has been described as a regulator of pilus biosynthesis (Dramsi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although important data have been published on their biogenesis and their function (Abbot et al, 2007;Dramsi et al, 2006;Gianfaldoni et al, 2007;Lauer et al, 2005;Maisey et al, 2007;Manetti et al, 2007;Mora et al, 2005;Rosini et al, 2006;Scott & Zähner, 2006;Telford et al, 2006), little is known about the regulation of their synthesis. Besides RogB (Dramsi et al, 2006;Gutekunst et al, 2003) SrtA has been described as a regulator of pilus biosynthesis (Dramsi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…GAS biofilm production is complex process influenced not only by environmental conditions such as ECM proteins, incubation temperature and medium, but also by many bacterial virulence factors such as capsule, SpeB, M protein, pili, etc. Manetti et al [37] assumed that on this multifactorial process also affect antigenic variation of M protein and pili, in addition to a variety known and poorly surveyed virulence factors, thus further complicating the already insufficiently elucidated process of biofilm assembling. Doern et al [38] suggested significance of in the timely manner production of several enzymes, such as SpeB, which in addition to his role in adhesion, is also one of the crucial factors in biofilm formation.…”
Section: Biofilmmentioning
confidence: 99%
“…The identification of pili in streptococcal species has only been recently published [98-100]. Pili of S. pyogenes serotype M1 promote adhesion to human tonsil epithelium and primary human keratinocytes and the formation of biofilm [101,102], while the pili proteins of S. agalactiae facilitate adherence and invasion of brain endothelium [103]. The pilus operons promoting synthesis and assembly of pili are found in genomic islands such as the FCT pathogenicity island in S. pyogenes [98], the rlrA pathogenicity island in S. pneumoniae [100,104], and in novel genomic islands in S. agalactiae [99,105].…”
Section: Pili-specific Secretion/assembly Pathwaymentioning
confidence: 99%